Analysis of Factors influencing the successful use of Massive Open Online Courses (MOOCs) to prepare Digital Talent - Muh Syaiful Romadhon; Betty Purwandari; Imairi Eitiveni; Mardiana Purwaningsih (Universitas Negeri Makassar, 2023)
One type of e-learning category is Massive Open Online Courses (MOOCs). MOOCs or MOOC promote the